2017
DOI: 10.1038/s41598-017-11151-x
|View full text |Cite
|
Sign up to set email alerts
|

Ligand activation induces different conformational changes in CXCR3 receptor isoforms as evidenced by plasmon waveguide resonance (PWR)

Abstract: The chemokine receptor CXCR3 plays important roles in angiogenesis, inflammation and cancer. Activation studies and biological functions of CXCR3 are complex due to the presence of spliced isoforms. CXCR3-A is known as a pro-tumor receptor whereas CXCR3-B exhibits anti-tumor properties. Here, we focused on the conformational change of CXCR3-A and CXCR3-B after agonist or antagonist binding using Plasmon Waveguide Resonance (PWR). Agonist stimulation induced an anisotropic response with very distinct conformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
4
15
0
Order By: Relevance
“…Therefore, the observed spectral changes can only be attributed to ligand‐induced receptor‐conformational changes. Such scenario has already been observed in previous PWR experiments involving ligand interaction with GPCRs . From PWR experiments, it was possible to determine a binding affinity of 0.8 n m between maraviroc and the CCR5 (Fig.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore, the observed spectral changes can only be attributed to ligand‐induced receptor‐conformational changes. Such scenario has already been observed in previous PWR experiments involving ligand interaction with GPCRs . From PWR experiments, it was possible to determine a binding affinity of 0.8 n m between maraviroc and the CCR5 (Fig.…”
Section: Resultssupporting
confidence: 70%
“…The present work, performed with wild‐type CCR5 produced via two alternative and completely independent sources, P. pastoris and cell‐free expression, simultaneously reveals Chol to significantly impact maraviroc affinity to the receptor with a 20‐ to 30‐fold decrease in affinity when Chol is present in the membrane. While one can argue that the impact in binding affinity is rather modest, very minor differences in receptor/ligand affinity have been shown to highly impact the selectivity of the activated signaling cascades in the case other chemokine receptors as the CXCR3 . This demonstrates the extremely thin fine‐tuning of GPCR activation and signaling.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that CXCL10 has a much greater binding affinity for CXCR3B compared to CXCL9 or CXCL11 while the affinity is similar between the three chemokines for the CXCR3A isoform 35 . This may be attributed to differences in special conformation between CXCR3A and CXCR3B 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Usually, such approaches are carried out by more than one approach and often rely on the use of a high quantity of material and also require labelled materials. PWR has been successful for studies of ligand-activation and receptor conformational changes [39,40,41,42,43], signaling [44,45], lipid impact [35,46], and domain partitioning [47] in GPCR activity, highly contributing to a better understanding the way such receptors function. The proposed methodology in this work provides higher contrast measurement in high speeds and high resolution, yet maintaining simplicity using a single laser diode and camera.…”
Section: Potential Applications Of the Proposed Methodologymentioning
confidence: 99%